(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Background: The early and accurate diagnosis of biliary atresia (BA) is critical for timely intervention. The triangularcordsign (TCS) onultrasonographyisavaluabletool, butitsdiagnosticperformancecanbevariable. Objective: To evaluate whether the use of operational diagnostic criteria (ODC) in conjunction with TCS enhances the screening accuracy for BA. Methods: A prospective cohort studz was conducted at MAGOsmani Medical College Hospital, Szlhetin Bangladesh from July 2021 to December 2022. A total of 60 infants with persistent jaundice underwent evaluation for biliary atresia via triangular cord sign, operational diagnostic criteria, and confirmation by intraoperative cholangiography. Data were analyzed with SPSS 23.0. Results: Among 60infants, biliary atresia was confirmed in 38 (63.3%).The triangularcord sign (TCS) showed 76.3% sensitivity and 86.4% specificity. Operational diagnostic criteria (ODC) alone demonstrated 89.5% sensitivity. Crucially, combining TCS and ODC (positive ifeither was positive) significantly enhancedsensitivity to97.4%(p<0.001) with aspecificity of 77.3%. Then egativepredictivevalueforthecombinedmodel was 94.4%, and its AUC of 0.94 was superior to either tool alone. Conclusion: The combination of operational diagnostic criteria with the triangular cord sign creates a highly sensitive and effective screening algorithm for biliary atresia. This integrated approach outperforms either method in isolation and can significantly enhance early detection, timely referral, and ultimately, improve outcomes for infants with this serious condition. Journal of Paediatric Surgeons of Bangladesh (2023) Vol. 14 (1 & 2): 31-35